Discriminatory Words in Written Outputs of Students in Junior High School - Fundivilla, Yharies; Alberto, Mercedita (International Journal of Arts, Sciences and Education, 2022)
The main purpose of the study is to determine the discriminatory words in written output of the students in junior high school. The respondents were composed of 100 grade 10 students of San Juan Integrated National High School during school year 2018-2019. Through descriptive evaluative method, the researcher used questionnaire and rubrics as main instruments in the study. The results were described in terms of frequency, percentage, rank, mean, mode, standard deviation, kurskal-wallis and spearman rho. The study revealed that most of the students are fifteen-year-old, female. However, in terms of parents’ educational attainment, most of the fathers are graduates of secondary education and most mothers are graduates of tertiary level. Likewise, most of the fathers are self-employed and most of the mothers are unemployed. In terms of the use of discriminatory words, it was found out that males, despite being lesser in number in the composition of respondents, tend to use blatant sexism compared to the female respondents; Although the students’ choice of words is more of blatant, it is not reflected in their written outputs which has very low usage of discriminatory words. The study concluded that: (1) There might be other factors that affect the student choice of words and their use of discriminatory words like cognitive, sociocultural and affective factors; (2) The students who are millennial are aware of discriminatory words and reflects sensitively to gender equality such that their written outputs do not include the use of blatant words.